1987
DOI: 10.2337/diacare.10.6.712
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intravenous Glucagon and Dextrose in Treatment of Severe Hypoglycemia in an Accident and Emergency Department

Abstract: Hypoglycemia is a serious problem in insulin-treated diabetic patients. In this study the efficacy of intravenous glucagon (1 mg) was compared with that of intravenous dextrose (25 g) in the treatment of hypoglycemia in insulin-treated patients attending an accident and emergency department. In addition, the prevailing glycemic control of these patients was compared with patients routinely attending a diabetic outpatient clinic. Both intravenous glucagon and dextrose were effective in the treatment of hypoglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 14 publications
0
45
1
Order By: Relevance
“…glucose). The study of Collier et al (1987) was performed with patients in an accident and emergency department, and therefore the insulin effect might be more protracted than in our study. Furthermore, the effect on glucose recovery of i.v.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…glucose). The study of Collier et al (1987) was performed with patients in an accident and emergency department, and therefore the insulin effect might be more protracted than in our study. Furthermore, the effect on glucose recovery of i.v.…”
Section: Discussionmentioning
confidence: 94%
“…and subcutaneous glucagon have been compared with each other and with oral and i.v. glucose (Collier et al, 1987;MacCuish et al, 1970;Muhlhauser et al, 1985 a,b; counterregulation Shipp et al, 1964). The glucagon in these studies derived from pancreas collection and extraction.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies were undertaken to understand how some plants which have action on the blood glucose. These plants may act on blood glucose through different mechanisms, some of them may have insulin like substances [Collier et al 1987], some may increase insulin output or inhibit the intestinal absorption of glucose or to the facilitation of metabolites in insulin dependent processes [Jia et al 2003]. Other may increase beta cells in the pancreas by activating regeneration of these cells [Shanmugasundaram et al 1990].…”
Section: In Vivo Biological Examinations Of Processed Cheese Analoguementioning
confidence: 99%
“…Again, data from the National EMS Information System (NEMSIS) regarding the pre-hospital EMS response to diabetic emergencies in the United States indicated that, in 2011, glucagon was administered 18,483 times in runs listed in the dataset, with 436 times requiring a repeat dose [54]; the Food and Drug Administration (FDA), and Health Canada, reported 82 and 8 failures out of a total of 568 reports from 2011 to 2012 and of 20 reports from 1997 to 2012, respectively [55,56]. Some authors, comparing IM glucagon to IV dextrose in the pre-hospital settings, showed a delay in recovering from an hypoglycemic event with glucagon [57][58][59][60], but with a steady increase in blood glucose [58]; in contrast, dextrose treated patients seemed to have more fluctuations of blood glucose.…”
Section: Introductionmentioning
confidence: 96%